Sizing and Design of PV Array for Photovoltaic Power Plant Connected Grid Inverter - Al-Shetwi, Ali Q.; Muhamad Zahim, Sujod (Universiti Malaysia Pahang, 2016)
Over the past few years, installation of photovoltaic power plants (PVPPs) are considered as one of the most promising technologies at many of countries around the world, in order to meet the growing demand of energy. The DC side (PV generators and MPPT) of a 1.5 MW PV power plant connected to the inverter is modeled and simulated using Matlab/Simulink. The sizing of the suggested PVPP is achieved, such as array sizing and enhanced perturb and observe maximum power point tracking (MPPT) technique, in order to overcome the disadvantages of conventional method such as oscillation and slowly tracking under sudden change of atmospheric conditions. The MATLAB/Simulink was run to simulate the PV array sizing and its characteristics depending on enhanced MPPT technique to improve the efficiency of the modules and getting maximum available power. The simulation result has been matched the sizing theoretical calculation results.